Wireless Stand‐Alone Trimodal Interactive Display Enabled by Direct Capacitive Coupling (Adv. Mater. 37/2022). Issue 37 (15th September 2022) - Jang, Jihye; Lee, Seung Won; Lee, Seokyeong; Lee, Chang Eun; Kim, Eui Hyuk; Jin, Wookyeong; Lee, Sejeong; Kim, Youngkyung; Oh, Jin Woo; Jung, Youngdoo; Kim, HoYeon; Yong, Hyungseok; et al.
Abstract : Interactive Displays A wireless stand‐alone trimodal interactive display is developed by Cheolmin Park and co‐workers, as reported in article number 2204760, where finger touch is displayed with three types of outputs of field‐induced electroluminescence, inverse piezoelectric sound, and tactile vibration, and remotely powered by the unique AC‐to‐AC power transfer based on direct capacitive coupling, making the device potentially suitable for a smart braille display.